Characterization of Autosomal Dominant Hypercholesterolemia Caused by PCSK9 Gain of Function Mutations and Its Specific Treatment With Alirocumab, a PCSK9 Monoclonal Antibody. (December 2015) - Hopkins, Paul N.; Defesche, Joep; Fouchier, Sigrid W.; Bruckert, Eric; Luc, Gérald; Cariou, Bertrand; Sjouke, Barbara; Leren, Trond P.; Harada-Shiba, Mariko; Mabuchi, Hiroshi; Rabès, Jean-Pierre; Carrié, Alain; et al.
Abstract : Background—: Patients with PCSK9 gene gain of function (GOF) mutations have a rare form of autosomal dominant hypercholesterolemia. However, data examining their clinical characteristics and geographic distribution are lacking. Furthermore, no randomized treatment study in this population has been reported. Methods and Results—: We compiled clinical characteristics of PCSK9 GOF mutation carriers in a multinational retrospective, cross-sectional, observational study. We then performed a randomized placebo-phase, double-blind study of alirocumab 150 mg administered subcutaneously every 2 weeks to 13 patients representing 4 different PCSK9 GOF mutations with low-density lipoprotein cholesterol (LDL-C) ≥70 mg/dL on their current lipid-lowering therapies at baseline. Observational study: among 164 patients, 16 different PCSK9 GOF mutations distributed throughout the gene were associated with varying severity of untreated LDL-C levels. Coronary artery disease was common (33%; average age of onset, 49.4 years), and untreated LDL-C concentrations were higher compared with matched carriers of mutations in the LDLR (n=2126) or apolipoprotein B (n=470) genes. Intervention study: in PCSK9 GOF mutation patients randomly assigned to receive alirocumab, mean percent reduction in LDL-C at 2 weeks was 62.5% ( P <0.0001) from baseline, 53.7% compared with placebo-treated PCSK9 GOF mutation patients ( P =0.0009; primary end point). After all subjects received 8 weeks of alirocumab treatment, LDL-C was reduced by 73% from baseline ( P <0.0001). Conclusions—: PCSK9 GOF mutation carriers have elevated LDL-C levels and are at high risk of premature cardiovascular disease. Alirocumab, a PCSK9 antibody, markedly lowers LDL-C levels and seems to be well tolerated in these patients. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique Identifier: NCT01604824. Abstract : Supplemental Digital Content is available in the text.